Nanostructured Ti–Ta thin films synthesized by combinatorial glancing angle sputter deposition. (11th November 2016) - Motemani, Yahya; Khare, Chinmay; Savan, Alan; Hans, Michael; Paulsen, Alexander; Frenzel, Jan; Somsen, Christoph; Mücklich, Frank; Eggeler, Gunther; Ludwig, Alfred
Abstract: Ti–Ta alloys are attractive materials for applications in actuators as well as biomedical implants. When fabricated as thin films, these alloys can potentially be employed as microactuators, components for micro-implantable devices and coatings on surgical implants. In this study, Ti100− x Ta x ( x  = 21, 30) nanocolumnar thin films are fabricated by glancing angle deposition (GLAD) at room temperature using Ti73 Ta27 and Ta sputter targets. Crystal structure, morphology and microstructure of the nanostructured thin films are systematically investigated by XRD, SEM and TEM, respectively. Nanocolumns of ∼150–160 nm in width are oriented perpendicular to the substrate for both Ti79 Ta21 and Ti70 Ta30 compositions. The disordered α ″ martensite phase with orthorhombic structure is formed in room temperature as-deposited thin films. The columns are found to be elongated small single crystals which are aligned perpendicular to the ( 20 4 ¯ ) and ( 204 ) planes of α ″ martensite, indicating that the films' growth orientation is mainly dominated by these crystallographic planes. Laser pre-patterned substrates are utilized to obtain periodic nanocolumnar arrays. The differences in seed pattern, and inter-seed distances lead to growth of multi-level porous nanostructures. Using a unique sputter deposition geometry consisting of Ti73 Ta27 and Ta sputter sources, a nanocolumnar Ti–Ta materials library was fabricated on a static substrate by a co-deposition process (combinatorial–GLAD approach). In this library, a composition spread developed between Ti72.8 Ta27.2 and Ti64.4 Ta35.6, as confirmed by high-throughput EDX analysis. The morphology over the materials library varies from well-isolated nanocolumns to fan-like nanocolumnar structures. The influence of two sputter sources is investigated by studying the resulting column angle on the materials library. The presented nanostructuring methods including the use of the GLAD technique along with pre-patterning and a combinatorial materials library fabrication strategy offer a promising technological approach for investigating Ti–Ta thin films for a range of applications. The proposed approaches can be similarly implemented for other materials systems which can benefit from the formation of a nanocolumnar morphology.